Studi Pengaruh Perubahan Kawasan Pesisir Pantai Merpati Terhadap Pariwisata Keberlanjutan di Kabupaten Bulukumba - Ika Fausia; Nurul Istiqomah Ulil Albab; Khairul Sani Usman (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2024)
Bulukumba Regency in South Sulawesi, known as "Butta Panrita Lopi," has utilized its coastal wealth, especially Merpati Beach, to develop tourism as one of the regional economic development strategies. The transformation of the Merpati Beach area from a slum area to a tourist destination and culinary center is part of the local government's strategic plan to improve MSMEs. This study aims to analyze the effect of changes in the Merpati Beach coastal area on sustainable tourism in Bulukumba Regency. This type of research is quantitative, namely the type of data in the form of numbers that can be processed using simple calculation methods. The sample in this study amounted to 88 samples, where sampling used a purposive sampling technique. This study uses primary data and secondary data obtained from observation, literature studies, documentation, interviews and questionnaires. The results of this study indicate that changes in the Merpati Beach coastal area have a significant impact on sustainable tourism in the form of economic, social and environmental aspects, such as business opportunities, job opportunities, changes in livelihoods, community income and environmental cleanliness. So the measurement method to see how strong the influence of variables on the influence of changes in coastal areas uses the Likert Scale approach. Furthermore, the results of the Chi-Square analysis/test will be matched with a scoring system on a Likert scale to determine the correlation of variables with their level of influence on community participation